Environmental efficiency of Japanese regions before and after the Great East Japan Earthquake - Satoshi Honma; Yoshiaki Ushifusa; Farhad Taghizadeh-Hesary; Soyoka Okamura; Lilu Vandercamme (Sustainable Futures)
Natural disasters can significantly impact environmental and economic performance through various channels, including infrastructure damage, supply chain disruptions, and changes in energy systems. While previous studies have examined isolated aspects of the Great East Japan Earthquake's (GEJE) environmental impact, a comprehensive analysis of regional environmental efficiency changes before and after this unprecedented disaster remains unexplored. This study employs a slacks-based measure data envelopment analysis model to evaluate the environmental and energy efficiency of 47 Japanese regions from 2005 to 2017. The model incorporates seven inputs (labor, capital, coal, oil, gas, renewables, and electricity), one desirable output (gross regional product), and four undesirable outputs (CO2, SOx, NOx, and dust). The study's results indicate that the mean environmental efficiency deteriorated from 0.529 in 2005 and 0.518 in 2008 (before GEJE), to 0.501 in 2011 and 0.464 in 2014 (after GEJE), but then improved to 0.527 in 2017. The earthquake severely damaged Iwate, Miyagi, and Fukushima in the Tohoku region, but these areas were inefficient even before the disaster. Kanto environmental efficiency deteriorated from unity in 2005 and 2008 to 0.839 in 2008 and 0.698 in 2011, then improved back to unity in 2017. The study also presents potential reduction ratios for energy and undesirable outputs. Panel Tobit regression analysis reveals that gross regional product per capita and tertiary industry share positively correlate with environmental efficiency, suggesting that economic development and service sector growth contribute to environmental improvement. These findings provide important insights for building environmentally resilient regional economies in disaster-prone areas.